2021
DOI: 10.20448/journal.501.2021.81.10.16
|View full text |Cite
|
Sign up to set email alerts
|

Aspects Hindering the Development and Survival of Small and Medium-Sized Enterprises in Pakistan: Stability Perspective

Abstract: This article intends to explore aspects that are hindering the development and survival of small and medium-sized enterprises (SMEs) in Pakistan. A survey was developed to collect statistics from 226 SME owners and staff in selected Punjab Provinces in Pakistan. Some statistical approaches accompanied the results of the survey to examine the elements hindering the development of SMEs in Pakistan. The results of the research indicate that the expected constraints, including lack of management knowledge, corrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…In the context of SMEs, economic sustainability is depicted as the most significant issue compared to other sustainability elements (Cardoni et al, 2020; Latif et al, 2023). This conundrum has spurred researchers to explore how SMEs might ensure their economic sustainability (Cantele & Zardini, 2018), specifically with Pakistani SMEs, where the dilemma of economic sustainability is at the forefront (Ali, 2021; Fatima & Bilal, 2020). Prior research has shown that several obstacles hinder the economic development of SMEs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of SMEs, economic sustainability is depicted as the most significant issue compared to other sustainability elements (Cardoni et al, 2020; Latif et al, 2023). This conundrum has spurred researchers to explore how SMEs might ensure their economic sustainability (Cantele & Zardini, 2018), specifically with Pakistani SMEs, where the dilemma of economic sustainability is at the forefront (Ali, 2021; Fatima & Bilal, 2020). Prior research has shown that several obstacles hinder the economic development of SMEs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Despite the importance of the SME sector, Pakistan’s economy is not benefiting to its full potential. The plausible explanation is that a high failure rate endangers Pakistan’s SME survival (Ali, 2021; Khan, 2022). Recently, Pakistan’s economic turmoil has begun to undermine the long-term survival of SMEs.…”
Section: Introductionmentioning
confidence: 99%